Analisis Pengaruh Tingkat Kesehatan Bank dengan Menggunakan Metode CAMEL terhadap Profitabilitas pada Sektor Perbankan Periode 2017–2021 - Andika, Andika (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study examines the effects of bank soundness indicators based on the CAMEL method on profitability in banking-sector companies listed on the Indonesia Stock Exchange during the 2017–2021 period. The study employs a quantitative descriptive approach using secondary data obtained from annual financial statements. The sample was selected through purposive sampling and consisted of 23 banking companies, resulting in 115 firm-year observations. Bank profitability was measured using Return on Assets, while bank soundness was represented by the Capital Adequacy Ratio, Non-Performing Loan ratio, Net Interest Margin, Operating Expenses to Operating Income ratio, and Loan-to-Deposit Ratio. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS. The results show that Net Interest Margin has a positive and significant effect on Return on Assets, while Operating Expenses to Operating Income has a negative and significant effect. Capital Adequacy Ratio, Non-Performing Loan ratio, and Loan-to-Deposit Ratio do not have significant effects on Return on Assets. Simultaneously, the five CAMEL indicators significantly affect bank profitability. The adjusted coefficient of determination is 87.5%, indicating that the research model explains 87.5% of the variation in Return on Assets.